Why Are People High in Dispositional Awe Happier? The Roles of Meaning in Life and Materialism - Zhao, Huanhuan; Zhang, Heyun; Xu, Yan; He, Wen; Lu, Jiamei (Frontiers in Psychology, 2019)
Awe is an intense emotional response to perceptually vast stimuli that dramatically transcend one’s ordinary reference frame and provoke a need to adjust the current mental structures. Dispositional awe reflects individual differences in the tendency to experience awe. The current study aims to examine the effect of dispositional awe on subjective well-being, with a focus on confirming the mediating role of meaning in life and materialism. A sample of five-hundred-and-sixty-three Chinese adults completed measures of dispositional awe, meaning in life, materialism, and subjective well-being. Correlation analysis revealed that dispositional awe, meaning in life, and materialism were all significantly correlated with subjective well-being. Structural equation modeling showed significant paths from dispositional awe to subjective well-being through both meaning in life and materialism. Bootstrap analysis also indicated that meaning in life and materialism mediated the relationship between dispositional awe and subjective well-being. These findings not only corroborate the critical role of dispositional awe in promoting subjective well-being, but also shed some light on why people high in dispositional awe are happier than those low in dispositional awe. Limitations and directions for future research were also discussed.